Towards an FDA-cleared basophil activation test - Alpan, Oral; Wasserman, Richard L.; Kim, Theodore; Darter, Amy; Shah, Atul; Jones, Douglas; McNeil, Donald; Li, Henry; Ispas, Laura; Rathkopf, Melinda; Perez, Elena; Siri, Dareen; et al. (Frontiers in Allergy, 2023)
Food allergy is a global health problem affecting up to 10% of the world population. Accurate diagnosis of food allergies, however, is still a major challenge in medical offices and for patients seeking alternative avenues of diagnosis. A flawless test to confirm or rule out a food allergy does not exist. The lack of optimum testing methods to establish precise clinical correlations remains a major obstacle to effective treatment. Certain IgE measurement methods, including component testing, have received FDA clearance, but they have been used primarily as an analytical tool and not to establish clinical correlations. Most allergy tests are still carried out within the laboratory, and skin tests outside a laboratory setting that are used for food allergy diagnosis rely on non-standardized allergens, according to the FDA definition. Epitope mapping and basophil activation test (BAT) have recently been proposed as a means of establishing better clinical correlations. Yet neither have received FDA clearance for widespread distribution. Of the two methods, the BAT has the advantage of being a functional assay. Over the past few years, several large private practice groups in the United States, have developed BAT as a clinical assay and have started using it in patient care. Given this clinical experience, the vast number of papers published on BAT (more than 1400 as of 2022) and the trend toward increasing FDA regulation, it is essential to understand the roadmap for regulatory clearance of this assay.